Kepemimpinan Kepala Sekolah Dalam Melaksanakan Program Pengembangan Sekolah Di SDIT Muhammadiyah Al-Kautsar Gumpang Tahun Ajaran 2016/2017 - Nurfarida, Siti Fila, Minsih, S.Ag., M.Pd (2017)
This study aims to identify (1) the role and tasks of school principals in implementing school development programs, (2) Principal strategies in implementing school development programs and (3) School development programs at SDIT Muhammadiyah Al-Kautsar. Data collection method in this research is by interview, observation and documentation. This research includes qualitative research with phenomenology design that is to study a visible phenomenon and then examine something that will be developed. The results of this study indicate that: (1) the principal has seven roles and professional duties as educators, managers, administrators, supervisors, leaders, innovators and motivators, (2) the main strategies that the principal must have in leadership performance include planning, organizing, supervision and evaluation, (3) the design and implementation of school development involves all school resources that include school principals, teachers, staff and school stakeholders.